Anodic Formation of Thick Anatase TiO2 Mesosponge Layers for High-Efficiency Photocatalysis - Lee, Kiyoung; Kim, Dam-Hee; Roy, Poulomi; Paramasivam, Indhumati; Birajdar, Balaji; Spiecker, Erdmann; Schmuki, Patrik (Journal of the American Chemical Society, 2010)
We report a process for the flabrication of an anatase TiO2 mesosponge (TMS) layer by an optimized Ti anodization process in a hot glycerol electrolyte followed by a suitable etching process. Such layers can easily be grown to > 10 mu m thickness and have regular channels and structural features in the 5-20 nm range. The layers show high photocatalytic activity and are mechanically very robust. The layers therefore open new pathways to the wide field of TiO2(anatase) applications.

Formation of a Non-Thickness-Limited Titanium Dioxide Mesosponge and its Use in Dye-Sensitized Solar Cells - Kim, Dam-Hee; Lee, Kiyoung; Roy, Poulomi; Birajdar, Balaji; Spiecker, Erdmann; Schmuki, Patrik (Angewandte Chemie International Edition, 2009)
Etch a sketch: Robust TiO_2 mesoporous layers can be fabricated on Ti surfaces by a combination of non-thickness-limited anodization and selective etching. Layers more than 50 extgreekmm thick with highly regular feature and pore sizes in the range 5–10 nm can be produced (see picture, FTO=fluorine doped tin oxide). The layers are highly flexible, well-adhered, and can be used directly after appropriate annealing in efficient dye-sensitized solar cells.
Keywords: dyes/pigments; mesoporous materials; solar cells; titanates; titanium

Front side illuminated dye-sensitized solar cells using anodic TiO2 mesoporous layers grown on FTO-glass - Lee, Kiyoung; Kim, Dam-Hee; Berger, Stefan; Kirchgeorg, Robin; Schmuki, Patrik (Electrochemistry Communications, 2012)
In the present work, we investigate the performance of anodic, self-organized TiO2 mesoporous structures (TMSs) in dye-sensitized solar cells (DSSCs) under front-side illumination conditions. In order to fabricate structures usable in a front-side (FS) configuration, TMSs were formed on FTO glass by a full anodic conversion of evaporated Ti films on the glass substrate in a glycerol/K2HPO4 electrolyte at 180 °C. The resulting mesoporous layers can be assembled to FS dye sensitized solar cells which show a thickness of only 3 extgreekmm and a remarkable efficiency of 4.34%. This is significantly higher than, for example, anodic TiO2 nanotubes of the same length even after efficiency enhancing TiCl4 treatments (3.01%). The best efficiency value for TMS-based DSSCs that we currently reached is for a 7 extgreekmm thick TMS layer, this is ≈6.82% which is highly promising for further improvements.
EAM Import::2019-03-14

Highly self-ordered nanochannel TiO2 structures by anodization in a hot glycerol electrolyte - Lee, Kiyoung; Kim, Dam-Hee; Schmuki, Patrik (Chemical Communications, 2011)
In the present work, we report on the self-organized growth of TiO2 layers consisting of a highly aligned nanochannel morphology. We show that an electrochemical anodization process of Ti in a hot glycerol/K2HPO4 electrolyte can be adjusted to yield these self-organized TiO2 structures. The channel diameter and length are controllable by the anodization parameters. This directional structure can, for example, find application in dye-sensitized solar cells.
EAM Import::2019-03-13

Improved efficiency of TiO2 nanotubes in dye sensitized solar cells by decoration with TiO2 nanoparticles - Roy, Poulomi; Kim, Dam-Hee; Paramasivam, Indhumati; Schmuki, Patrik (Electrochemistry Communications, 2009)
In the present work we investigate the effect of TiCl_4 treatments on the photoconversion efficiency of TiO_2 arrays used in dye sensitized solar cell. The results clearly show that by an appropriate treatment the decoration of the TiO_2 nanotube arrays with TiO_2 nanocrystallites of a typical size of 3 nm can be achieved. These particles can be converted to mixture of anatase and rutile phase by annealing in air. This decoration of the TiO_2 nanotubes leads to a significantly higher specific dye loading and, for certain annealing treatments, to a doubling of the solar cell efficiency (in our case from 1.9% to 3.8% of AM 1.5 conditions) can be achieved.
EAM Import::2019-03-13

Nb doping of TiO2 nanotubes for an enhanced efficiency of dye-sensitized solar cells - Yang, Mingjun; Kim, Dam-Hee; Jha, Himendra; Lee, Kiyoung; Paul, Jonathan; Schmuki, Patrik (Chemical Communications, 2011)
Nb-doped TiO2 nanotube (with CNb < 1 wt%) layers were successfully fabricated by self-ordered electrochemical anodization of Ti–Nb alloys. When used in dye-sensitized solar cells the efficiency enhanced by up to 30% compared to non-doped TiO2 nanotubes. IMVS measurements indicate the beneficial effect to be due to lower recombination losses.
EAM Import::2019-03-12

TiO2-WO3 Composite Nanotubes by Alloy Anodization: Growth and Enhanced Electrochromic Properties - Nah, Yoon-Chae; Ghicov, Andrei; Kim, Dam-Hee; Berger, Stefan; Schmuki, Patrik (Journal of the American Chemical Society, 2008)
The present work demonstrates that uniform and highly ordered arrays of TiO_2-WO_3 nanotubes can be grown by anodization of Ti alloys in an ethylene glycol/fluoride based electrolyte under selected electrochemical conditions. These aligned mixed oxide nanotube structures are highly suitable for enhanced electrochromic reactions; in particular we show that already small amounts of WO_3 (such as 0.2 at%) present in the tube oxide drastically improve the electrochromic properties (contrast, onset potential, cycling stability) of nanotube layer based devices.
EAM Import::2019-03-13

TiO2 nanotubes and their application in dye-sensitized solar cells - Roy, Poulomi; Kim, Dam-Hee; Lee, Kiyoung; Spiecker, Erdmann; Schmuki, Patrik (Nanoscale, 2010)
The present article reviews the current status of using TiO2 nanotubes in Gratzel-type, dye-sensitized solar cells and extends the overview with the latest results and findings. Critical factors in tube geometry (length, diameter, top morphology), crystal structure (amorphous, anatase, rutile) as well as factors affecting dye loading or electron mobility are addressed. The highest solar cell efficiencies today for pure nanotube systems reach approximately 4% while for some mixed systems, around 7% has been reported. For both Systems significant room for enhancement is anticipated and some key points and strategies for improvement are outlined.